Performance of state-owned enterprises in Indonesia: The impact of government involvement - Puspasari, Rahayu (Curtin University, 2014)
The study investigates whether government intervention in Indonesian State Owned Enterprises (SOEs) governance, financial, and regulatory framework impact on performance. Agency theory is used to construct the ten hypotheses. The 125 SOEs are examined using data from 2007-2009 SOE financial reports and government documents. Semi-structured interviews are conducted to corroborate findings of the main analysis. The quantitative findings and interview results support noting strong government involvement in the SOEs various governance, financial and regulatory activities.